HOW TO TEACH FOREIGN LANGUAGES (GENERAL REMARKS) - Khasanova , Zarrina Shadiyarovna (Educational Research in Universal Sciences, 2023)
The Recent reforms in foreign language teaching in Uzbekistan are mainly focused on teaching English at all levels and stages of education. In this regard, CEFR serves as the main basis for the development of a national standard. Today, there is a growing interest among students in learning English and other foreign languages, as evidenced by the growing desire of students to obtain international CEFR and IELTS certificates. In this course, we will discuss importance and rules of teaching foreign languages which are considered to be the most useful for those who are willing to teach languages in a really communicative way.